Development of Pencak Silat Learning Media Based on Android Applications for Students - Mujiburrahman; Yudhi Teguh Pambudi; Arfin Deri Listiandi; Rifqi Festiawan; Dewi Anggraeni (Media Ilmu Keolahragaan Indonesia, 2025)
Abstract Physical Education, Sports and Health still uses conventional approaches, such as lectures, discussions and assignments, but teachers have not used technology to improve their learning. The aim of this research is to create pencak silat learning media that students can use via an Android application. Research and development (R&D) is carried out using the ADDIE model, which consists of several stages: 1) Analysis (Analysis), 2) Design (Designing), 3) Development (Development), 4) Implementation (Application), and 5) Evaluation (Evaluation). This research used a sample of students from Madrasah Aliyah Negeri 3 Cilacap and Ma'arif NU 1 Kemranjen High School. Quantitative descriptive analysis was used to analyze the data. Based on the assessments of several experts—material, media, and language—it can be concluded that the learning media created is very suitable for use. The media expert's score was 87% with "very feasible" criteria, the material expert's assessment was 94% with "very feasible" criteria, the language expert's score was 100% with "very feasible" criteria, and the small and large scales test score was 91% with "very feasible" criteria.